Consolidation chemotherapy may improve pathological complete response for locally advanced rectal cancer after neoadjuvant chemoradiotherapy: a retrospective study - Cui,Jin; Dou,Xue; Sun,Yanlai; Yue,Jinbo (PeerJ, 2020)
Background Patients with locally advanced rectal cancer (LARC) have an improved prognosis if achieved a pathological complete response (pCR) on account of neoadjuvant chemoradiation therapy (nCRT). However, the proportion of patients achieving pCR is only 8–24%. The purpose of this study was to explore whether the addition of consolidation chemotherapy to nCRT could improve pCR rate in patients with LARC. Materials and Methods The subjects were 144 individuals with clinical stage II (T3–4, N0) or III (any T, N1–2) LARC who had received neoadjuvant CRT followed by total mesorectal excision (TME). Eighty-three patients in the consolidation chemotherapy group received two cycles XELOX between CRT and TME, while 61 patients in the standard treatment group without consolidation chemotherapy. The pCR (ypT0N0), tumor downstaging (ypT0-2N0) after TME and adverse events (AEs) during and post treatment were compared between the treatment groups using multivariable logistic regression analysis. To adjust the unbalanced variables for the primary endpoint, logistic regression analysis and stratified analysis were performed. Results The consolidation chemotherapy group improved pCR rate (19.3% vs 4.9%, p = 0.01) and tumor downstaging rate (45.8% vs 24.6%, p = 0.009) compared to the standard treatment group. After adjustment for clinical tumor stage, clinical nodal stage and time interval to surgery, patients with consolidation chemotherapy were more likely to reach pCR (adjusted odds ratio 4.91, 95% CI [1.01–23.79], p = 0.048). AEs during and post treatment in the two groups were 54.1% vs 49.3% (p = 0.57), respectively. In addition, the incidence of any grade 1–2 AEs in the two groups was 93.4% vs 95.1% (p = 0.93), while the incidence of grade 3 AEs was 1.6% versus 2.4% (p = 0.74), respectively. No grade 4 AEs occurred in two groups. Conclusions The addition of neoadjuvant consolidation chemotherapy after CRT significantly increased the pCR rate and did not increase the AEs during and post treatment and in patients with LARC.
Keywords: Colorectal cancer; Consolidation chemotherapy; pCR; Tumor downstaging; Neoadjuvant chemoradiotherapy; TME